ความก้าวหน้าในอาชีพของข้าราชการครูและบุคลากรทางการศึกษาของสำนักงานเขตพื้นที่การศึกษาประถมศึกษาเชียงใหม่ เขต 6 - ศิริรักษ์ ทิพย์วิวัฒน์พจนา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The study titled “Career Progression of Government Teachers and Educational Personnel of Chiang Mai Primary Educational Service Area Office 6”, had two objectives: 1) to analyze career progression of government teachers and educational personnel of Chiang Mai Primary Educational Service Area Office 6; and 2) to compare the opinions of government teachers and educational personnel towards the profession of government teachers and educational personnel of Chiang Mai Primary Educational Service Area Office 6, divided by positions. Regarding the results, it was found that samples who were government teachers (in the teaching field) and education administrators deemed that they had progression on promotion and salary increases as they grew by developing their work according to their fields. Their salaries increased in certain accordance with the royal decree on salary increases. In terms of opportunity to develop self-progression, they should increase their knowledge for advancement to higher positions and higher responsibility. In contrast, other education personnel in section 38 Kor.(2) had less progression in their positions. There were few high positions shaped like a pyramid. Their salaries were raised according to the regulation of the office of the Civil Service Commission. In terms of the relationship among the superiors and colleagues, every position agreed that encounters with superiors can affect their progressions for promotion and salary increases because the superiors are authorized to directly consider their virtues and suitability. Regarding the hypothesis testing, it was found that the significant value was equal to 0.00, which was opposite to the main hypothesis which stated that government teachers and educational personnel who have different positions had the different opinions towards career professions with the difference at a statistical significance level of 0.05. Recommendations 1.Progressions among work fields should be studied and compared to provide understanding about the differences of progressions in each field. 2.Regarding the results, it was found that the all three aspects of career progression - salary increases progression, self-progression development, and relationships among superiors and colleagues - were at high levels. However, progression for getting promotion was at a medium level. The questions might have been unclear and the questionnaire respondents could have misunderstood the questions. Therefore, the questions should be made clearer. 3.Rules and regulations regarding human resources management should be studied for further understanding.